Oikos Quilombola : arte-educação-ambiental e a poética do pau a pique - Ferreira, Carlos Roberto (2020)
The socio-environmental sense of the Casa da Cultura Quilombola as an Oikos – inhabited space of the house – was interpreted in the Quilombo political dimension. Oikos as a space of the teacher and student’s praxiological dialogue, in the architectures of Education. Communion of the family in their cultural environment, in the intimate daily life, in the Mata Cavalo community, in the municipality of Nossa Senhora do Livramento – MT. The investigative understanding was reframed as a reference space of the school and local culture, constructed through Pedagogical Practice, supported by Environmental-art-education and its praxis. The Cartography of the Imaginary was the phenomenological basis as a methodology, which combined bricks of different knowledge through Participant Observation and Community School Environment Project – PAEC. The dialogue with Art-education was made with clay-saliva, an intrinsic element in the Formation Process with the Cartography of Fire. This dialogical relationship contributed to the investigation of physical environmental catastrophes present in the Casa da Cultura, caused by local climate collapses. With the participation of Teachers, Technicians, students and people from the Community we achieved our Greater Objective, when we sought to investigate the Casa da Cultura Quilombola in the dimension of an Oikos, observing its pedagogical relationship with the School, to find in environmental-art-education, a direct relationship between the School and the Community. Also, understanding how quilombolas interpret the climatic phenomenon, though invisible, makes it difficult to be questioned to warn about socio-environmental catastrophes. The research brought me knowledge to scientific life and my professional daily life as an art-environmental educator; it contributed to my thought on the School socioenvironmental role, as well as it revealed reflections to understand the richness of the cultural dimension, present in the quilombola family’s experiences. Inside this Oikos, I drank from the clay pot the water of formation, in search of a scientific trip. I faced the “painful” process of deformation, trying to overcome the obstacles with earth force. Likewise, I turned myself into the combustion of the desired change with the force of fire and finally, I had time to rest in search of a reformation. However, it was the interviews and their responses that signaled that in this research, there was another time to be respected: that kept in the quilombola resistance experiences, present in inhabiting a wattle and daub house, in the courage to leave the fire outside. With that thought, I activated and re-activated the memory, in order to breathe the air of a new cycle, taking into account the enchantment and reenchantment of the research process in the Oikos that we inhabit.